2014
DOI: 10.1111/apt.12928
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to infliximab in paediatric perianal Crohn's disease

Abstract: SUMMARY BackgroundIt is reported that 27-54% of paediatric patients with perianal Crohn's disease (CD) do not respond to infliximab (IFX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…[22][23][24] IFX is recommended as an induction and maintenance treatment for CD patients with PD, 25 and Dupont-Lucas et al reported that 75% of older pediatric patients responded well to IFX treatment, and their PD had improved by 1 year. 26 Four of five patients with NUC-PD responded to IFX with a significant improvement in perianal disease. However, despite the response to IFX, severely destructive perianal lesions may eventually require ostomy placement for the early loss of response or sphincter destruction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[22][23][24] IFX is recommended as an induction and maintenance treatment for CD patients with PD, 25 and Dupont-Lucas et al reported that 75% of older pediatric patients responded well to IFX treatment, and their PD had improved by 1 year. 26 Four of five patients with NUC-PD responded to IFX with a significant improvement in perianal disease. However, despite the response to IFX, severely destructive perianal lesions may eventually require ostomy placement for the early loss of response or sphincter destruction.…”
Section: Discussionmentioning
confidence: 91%
“…IFX is recommended as an induction and maintenance treatment for CD patients with PD, and Dupont‐Lucas et al . reported that 75% of older pediatric patients responded well to IFX treatment, and their PD had improved by 1 year . Four of five patients with NUC‐PD responded to IFX with a significant improvement in perianal disease.…”
Section: Discussionmentioning
confidence: 99%
“… 40 41 Infliximab improved outcomes of perianal CD with response rates of 75% and remission rates of 50% at 1 year. 42 Adalimumab achieved 1-year remission rates of 45% in anti-TNFα antibody naïve children and 20% in infliximab non-responders. 43 …”
Section: Maintenance Of Remissionmentioning
confidence: 97%
“…40 41 Infliximab improved outcomes of perianal CD with response rates of 75% and remission rates of 50% at 1 year. 42 Adalimumab achieved 1-year remission rates of 45% in anti-TNFα antibody naïve children and 20% in infliximab non-responders. 43 Infliximab is first administered intravenously in doses of 5 mg/kg at weeks zero, two and six followed by 8-weekly infusions.…”
Section: Anti-tnfα Antibodiesmentioning
confidence: 97%